Bivalve community structure in relation to soil and porewater properties in Benoa Bay, Bali, Indonesia - GEDE SURYA INDRAWAN; I WAYAN ARTHANA; NI MADE SUARTINI; I GEDE HENDRAWAN; I PUTU SUGIANA (Society for Indonesian Biodiversity, 2026)
Abstract. Indrawan GS, Arthana IW, Suartini NM, Hendrawan IG, Sugiana IP. 2026. Bivalve community structure in relation to soil and porewater properties in Benoa Bay, Bali, Indonesia. Biodiversitas 27 (3): d270301. https://doi.org/10.13057/biodiv/d270301. Coastal ecosystems support benthic communities that are sensitive to environmental changes, making bivalve community structure a reliable indicator of ecological condition. This study examined relationships between bivalve community structure and soil and porewater properties at seven stations in Benoa Bay, Bali (n: 7 stations). Bivalve sampling used a transect-quadrat approach and recorded 19 species, with spatial variation in richness and density. Soil parameters included total organic matter (TOM, 2.55-4.60%), pH (6.05-6.89), soil fractions (gravel, sand, silt, clay), and water content (0.32-0.59). Porewater properties measured at 30-60 cm depth included temperature (26.1-28.1°C), pH (6.27-7.17), salinity (23.1-28.9 ppt), redox potential (-51 to -98 mV), and dissolved oxygen (1.01-2.63 mg L⁻¹). Data normality was assessed using the Shapiro-Wilk test, followed by Pearson correlation analysis and linear regression. Bivalve density showed a significant positive correlation with sand fraction (r: 0.84, p<0.05) and dissolved oxygen (r: 0.85, p<0.05). Positive but non-significant trends were observed for salinity (r: 0.58, p: 0.172) and oxidation-reduction potential (r: 0.72, p: 0.068), while negative but non-significant relationships occurred with silt (r: -0.65, p: 0.114) and clay fractions (r: -0.73, p: 0.062). Community structure varied spatially, with Shannon diversity index values ranging from 0.58 to 1.80, indicating conditions from relatively balanced to stressed assemblages. Given the limited number of stations, these correlations should be interpreted as exploratory rather than definitive. These results indicate statistically significant associations between bivalve density and selected environmental variables. The findings suggest that bivalve community metrics, combined with soil and porewater measurements, may help describe spatial variation in estuarine ecosystem condition.